Unusual presentation of firework injury causing intraoral burns - K Patel Chintan; P Suri Manav; C Raibagkar Santosh; R Mehta Devesh (Indian Journal of Plastic Surgery)
Fireworks are commonly used in celebrate festive occasions. We present a case of an unusual presentation of intraoral firework injury, which is a very rare case. A fifteen year old boy kept four explosive papercaps wrapped in a small polythene bags in between his left molars and crushed them. This resulted in a contused lacerated wound over the left buccal mucosa. Patient was treated conservatively with maintenance of intraoral hygiene, antibiotics, proteolytic enzymes and analgesics. It took 18 days for complete healing of the wound.